The use of ibrutinib before and after allogeneic stem cell transplantation. (3rd April 2019) - Martino, Massimo; Ferreri, Anna; Naso, Virginia; Moscato, Tiziana; Loteta, Barbara; Gentile, Massimo; Morabito, Antonella; Provenzano, Fabio; Cimminiello, Michele; Carella, Angelo Michele; Console, Giuseppe; Recchia, Anna Grazia
ABSTRACT: Background : FDA designated ibrutinib as a breakthrough therapy in Mantle Cell Lymphoma (MCL) and Chronic Lymphocytic Leukemia (CLL). Nevertheless, patients who progress under ibrutinib still have a poor prognosis. In this setting, allogeneic hematopoietic stem cell transplantation (allo-HSCT) could induce long-term disease control. Areas covered : The purpose of the present review is to provide information on the efficacy of ibrutinib when administered before and after allo-HSCT for CLL and MCL. Moreover, we will focus on the current role of ibrutinib for chronic GVHD. Expert opinion : Ibrutinib as bridge to allo-HSCT does not appear to affect the safety of the treatment in patients with CLL and MCL. Current evidence support further evaluation of ibrutinib for the treatment of relapsed CLL and MCL after allo-HSCT. In this setting, ibrutinib should be not only highly efficient on CLL and MCL cells but might also have the ability to enhance the activity of donor T cells. Chronic GVHD is the most common long-term complication following allo-HSCT. Results from a phase 2 clinical trial culminated in the FDA-approval of ibrutinib as second-line therapy of steroid-refractory or steroid-resistant chronic GVHD. A randomized, controlled trial in patients with chronic GVHD should be performed.